Perspectives on genetic discrimination - Lemke, Thomas (Routledge advances in sociology, 2013)
Over the past 15 years, a series of empirical studies in different countries have shown that our increasing genetic knowledge leads to new forms of exclusion, disadvantaging and stigmatization. The spectrum of this ""genetic discrimination"" ranges from disadvantages at work, via problems with insurance policies, to difficulties with adoption agencies. The empirical studies on the problem of genetic discrimination have not gone unnoticed. Since the beginning of the 1990s, a series of legislative initiatives and statements, both on the national level and on the part of international a.